Pengaruh Transparansi, Kompetensi, Sistem Pengendalian Internal, Pemanfaatan Teknologi Informasi dan Partisipasi Masyarakat Terhadap Akuntabilitas Pengelolaan Dana Desa - Permata Salsabilla Dapersal; Rasyidah Mustika; Wiwik Andriani (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This research aims to determine the impact of transparency, competence, internal control systems, utilization of information technology, and community participation on the accountability of village fund management in Barangin District, Sawahlunto City. This research uses a quantitative approach with a survey method by distributing questionnaires to 6 villages. The sample consisted of 80 respondents, including village heads, village secretaries, members of the village consultative body, finance heads, planning heads, general administration heads, governance heads, welfare heads, public service heads, and hamlet heads. The sampling technique used is purposive sampling. The analysis technique applied is multiple linear regression using SPSS version 25.0. The results show that transparency and competence have a positive and significant effect on the accountability of village fund management in Barangin District, Sawahlunto City. Meanwhile, internal control systems, utilization of information technology, and community participation do not have a significant effect on the accountability of village fund management in Barangin District, Sawahlunto City